L’organisation du travail universitaire des étudiant·e·s en situation de handicap et son accompagnement. Étude de cas en France et en Angleterre - Micha Louisa Mettouchi (Éducation et Socialisation)
This article focuses on the organization of university work of English and French students with disabilities and the way in which the university environment sees the birth of and responds to the difficulties in this area, involving restrictions of participation in learning and situations of inequality.We will find that for some students an efficient organization of work is possible thanks to the resources that we will highlight. On the other hand, for other students the strategies implemented are ineffective for reasons that we will explain, as well as their consequences for student careers.As such, we will make recommendations to support these student practices, the challenge of which lies in belonging to the university and academic success.